School Management and its Impact on the Implementation of Educational Inclusion Policies in Ecuador - Díaz Suárez, Darwin Javier; Cajas Cajas, Wilson Ivan; Guerrero Vaca, Jeniffer Pamela; Maila Villa, Angel Rolando; Gavin Bautista, Patricia Janeth (Revista Ecos de la Academia, 2025)
This study aimed to systematize and critically analyze the empirical and theoretical evidence on how school management influences the implementation of inclusive education policies in Ecuador. A systematic review was conducted following the PRISMA 2020 Statement, with the protocol registered on the Open Science Framework (OSF). Boolean search strategies were applied in databases such as Redalyc, ERIC, SCIELO, and Google Scholar, identifying 2,680 initial studies. After a rigorous screening process, 18 studies met the inclusion criteria. Evidence was synthesized through a qualitative descriptive and interpretative analysis. Methodological quality was assessed using standardized tools: MMAT for mixed-methods studies, STROBE for non-randomized quantitative studies, and AMSTAR-2 for systematic reviews. The findings were organized into five dimensions: pedagogical leadership and governance, teacher training and human resources, infrastructure and accessibility, organizational culture and school climate, and monitoring and continuous improvement. Results indicate that while Ecuador has a solid legal framework and emerging practices of transformational leadership, significant challenges remain in teacher training, provision of adapted resources, and inclusive evaluation mechanisms. The study concludes that school management plays a decisive role in translating legal frameworks into sustainable practices, but requires more flexible governance models, ongoing teacher development, and adequate resources to consolidate inclusive processes.